Poder político e lutas de classes na Venezuela: 1989 2009 - Klein, José Alfonso (2010)
This José Alfonso Klein s research presents a theoretical reflection on Political Power and Classes Struggles in Venezuela: 1989 2009. Initially, it was considered whether the deployment of neoliberal policies as determinative for configuring economic, political and social history of that period, in Latin America. In parallel movement, it can be observed developments of the imposition of this new mode of capitalist development: economic crisis, political instability, popular insurgencies. In the region of Latin America and the Caribbean, Venezuela has presented as main field of proliferation of popular movements to combat the deterioration of life general conditions of the working class, produced by inconsequentional economical opening, since 1989. The economic crisis caused social conflicts, which awaken political arguing. In Venezuela, the first and crucial moment of contestation of the masses against neoliberalism and imperialism (Caracazo), defined the history direction. The political organization for social movements follow Practical and theoretical, according to the reflection of historical agents at the time, can lead to a struggle for the revolutionary field or conciliatory. In the Venezuelan issue, the actions and ideas was designed by the so called the Bolivarian Revolution , led by President Hugo Chávez, which signals policies related to structural socioeconomic reforms. Consequently, the reaction of the former politically hegemonic classes has faded in an obvious class struggle, which culminated in a strike against Chavez -and counter-attack of the masses and part of the army in their favor (2002). In addition to the consideration of the political purposes of protests from "Street policy (governists or opposition), the evaluation of this process requires observation of socio-economic results of Government "revolutionary Bolivarian", presented in statistical surveys (until 2009). However, a simple review of the current economic situation of Venezuela certainly will not answer questions such as: the dimension of the correlation of forces; the degree of revolutionary forces accumulated; the ability to action or reaction of the classes in defense of their interests; the deepening of classes s struggle in the country depends on the capacity of reforms that are suggested as being "revolutionary", caused by a more violent reactions that may occur.The perception of the entire process will depend on the capacity of the social forces in concreting and operating transformations necessary for setting up a new Venezuelan reality. For both, not just a passive observer, but the active participation of this historic moment which is the major purpose of this work